2021
DOI: 10.3390/cancers13184624
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning for Precision Oncology

Abstract: Precision oncology is grounded in the increasing understanding of genetic and molecular mechanisms that underly malignant disease and offer different treatment pathways for the individual patient. The growing complexity of medical data has led to the implementation of machine learning techniques that are vastly applied for risk assessment and outcome prediction using either supervised or unsupervised learning. Still largely overlooked is reinforcement learning (RL) that addresses sequential tasks by exploring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…Our research showed that women who participated in organized two-cancer screening reported a high level of overall perceived usefulness of the screening program, and its association with the willingness to participate in screening again and to recommend screening to others was statistically significant. As the final step in organized two-cancer screening, overall perceived usefulness can help participating women gain peace of mind by dispelling doubts, anxiety, and worry about two-cancer, which would be a reinforcer for screening participation [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research showed that women who participated in organized two-cancer screening reported a high level of overall perceived usefulness of the screening program, and its association with the willingness to participate in screening again and to recommend screening to others was statistically significant. As the final step in organized two-cancer screening, overall perceived usefulness can help participating women gain peace of mind by dispelling doubts, anxiety, and worry about two-cancer, which would be a reinforcer for screening participation [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of the algorithm is to maximize the rewards. RL applications in oncology have been proposed, for instance, in the domain of detection of lung nodules [ 22 ], and while potentially a tool for supporting clinical decisions, a few challenges have been discussed in precision oncology [ 23 ], treatment [ 24 ], personalized dose optimization [ 25 ] and model-informed precision dosing [ 26 ].…”
Section: Data Integrationmentioning
confidence: 99%
“…The use of graph-linked unified embedding (GLUE) introduced the generative learning strategy of the variational graph autoencoder (VGAE) algorithm to realize the unsupervised integration and regulatory inference of millions of single-cell multi-omics data, with high efficiency and accuracy (Cao & Gao, 2022). Still, a number of promising ML approaches, such as PU-learning (Li et al, 2022), contrastive learning (Chen et al, 2020) and reinforcement learning (Eckardt et al, 2021), which have succeeded in the areas of human genomics, computer vison and games, respectively, need further exploration in plant research. There is no doubt that the increasing application of advanced algorithms will further promote plant systems biology research.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%